"Rada Narodowościowa" and national minorities in Eastern nations during World War II = Rada Narodowościowa wobec mniejszości narodowych i narodów wschodnich w czasie II wojny światowej - Miszewski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the problem of ethnic policy of the Polish government in exile against minorities and nations of Eastern Europe. Presents the content of newspaper articles from the period of the Second World War ("Rzeczpospolita Polska", "Kraj", "Głos Polsko-Ukraiński") and official documents ("Uwagi o naszej polityce międzynarodowej"), in which they discussed the current policies, visions of future ethnic relations in post-war Poland.
Keywords: Rada Narodowościowa; nation minorities; Sikorski, Władysław, gen. (1881-1943); mniejszości narodowe